Political participation of students of Pedagogy from the Universidade Estadual de Ponta Grossa (Práxis Educativa, 2018)
This text aims to discuss the participation of students of the Pedagogy course from the Universidade Estadual de Ponta Grossa (UEPG), Paraná, Brazil, on issues related to politics. The theoretical-methodological framework adopted in the research was the historical-dialectical materialism, which allows to understand the reality from its concrete totality. The data collection counted on the elaboration and application of a questionnaire with ten open questions, answered by 51 students from the course. The data analysis points to a context of demobilization and individualization of actions, and also the demonstration, by a significant number of the subjects that participated in the research, of disbelief regarding the effectiveness of participation in political activities. Keywords: Work. Education. Political participation.